2016
DOI: 10.1007/jhep04(2016)046
|View full text |Cite
|
Sign up to set email alerts
|

The scalar triplet contribution to lepton flavour violation and neutrinoless double beta decay in Left-Right Symmetric Model

Abstract: We analyse in detail the scalar triplet contribution to the low-energy lepton flavour violating (LFV) and lepton number violating (LNV) processes within a TeV-scale left-right symmetric framework. We show that in both type-I and type-II seesaw dominance for the light neutrino masses, the triplet of mass comparable to or smaller than the largest right-handed neutrino mass scale can give sizeable contribution to the LFV processes, except in the quasi-degenerate limit of light neutrino masses, where a suppression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 153 publications
(234 reference statements)
3
43
1
Order By: Relevance
“…It can be seen from the plots shown in figure 6, 7 and 9 that this parameter can be larger than unity, implying that the doubly charged scalar masses can be as small as the heaviest right handed neutrino mass which can keep the scalar triplet masses well within the reach of LHC. This is in contrast to earlier results of [32] showing the scalar triplet to be at least ten times heavier than the heaviest right handed neutrino and the more recent work [57] where r was shown to be close to unity for a very small range of lightest neutrino mass. As can be seen from the plot in figure 7, we can have r ≥ 1 for almost all values of lightest neutrino mass in case of inverted hierarchy.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…It can be seen from the plots shown in figure 6, 7 and 9 that this parameter can be larger than unity, implying that the doubly charged scalar masses can be as small as the heaviest right handed neutrino mass which can keep the scalar triplet masses well within the reach of LHC. This is in contrast to earlier results of [32] showing the scalar triplet to be at least ten times heavier than the heaviest right handed neutrino and the more recent work [57] where r was shown to be close to unity for a very small range of lightest neutrino mass. As can be seen from the plot in figure 7, we can have r ≥ 1 for almost all values of lightest neutrino mass in case of inverted hierarchy.…”
Section: Resultscontrasting
confidence: 99%
“…To be more specific, the authors of [57] showed that for heaviest right handed neutrino mass as low as 400 GeV, the triplet scalars are allowed to be as low as around 800 GeV for right handed charged gauge boson mass 3.5 TeV. Here we extend both these works [56,57] by considering more general type I and type II seesaw terms with comparable strength and study their implications in LFV processes µ → 3e, µ → eγ and LNV process like 0νββ. Instead of considering any specific mass matrix structure for either type I or type II seesaw mass matrix, we consider a very general mass matrix for one of the seesaw terms.…”
Section: Jhep07(2016)022supporting
confidence: 55%
See 3 more Smart Citations